Estimation of Standing State Biomass and Carbon Sequestration Potential of Multipurpose Tree Species at Mohand Range, Dehradun Forest Division, Uttarakhand - Sharma, Vishwajeet; Patel, Pradeep Kumar; Kumar, Devendra (Indian Forester, 2016)
The present study was carried out on 24-yr-old five multipurpose tree species viz, Acacia nilotica (L.) Delile, Albizzia lebbeck (L.) Benth., Dalbergia sissoo D.C., Eucalyptus tereticornis Sm. and Terminalia arjuna (Roxb. ex. DC.) Wight&Arn. with an objective to estimate above ground biomass and carbon sequestration potential at Mohand range, Dehradun Forest Division, during 2011-2012. Aboveground biomass production was observed to be maximum in Eucalyptus tereticornis (827.12 kg /tree) and the minimum was in Terminalia arjuna (450.80 kg/tree). Results of fixed carbon percentage showed Albizzia lebbeck and Dalbergia sissoo as most suitable multipurpose tree species. The maximum fixed carbon content or carbon storage per cent was observed in Albizzia lebbeck (56.68%) while minimum was in Eucalyptus tereticornis (48.75%). The maximum amount of carbon sequestered was recorded in Eucalyptus tereticornis (403.40 kg/tree) and the lowest was n Terminalia arjuna (248.45 kg/tree). It was recorded that the amount of carbon dioxide sequestered was highest in Eucalyptus tereticornis (1478.85 kg/tree), whereas, the lowest amount was recorded in Terminalia arjuna (910.83 kg/tree).